ANALISIS PENENTUAN HARGA ASET PADA PASAR MODAL ASIA PASIFIK: LOKAL ATAU GLOBAL? - Sukasmanto Sukasmanto (Journal of Indonesian Economy and Business (JIEB), 2004)
The purposes of this study are to identify the empirical evidence whether the pricingerror from using domestic CAPM when the use of global CAPM is appropriate, whether thesecurity risk that is diversifiable domestically is also diversifiable globally, and whether theuse of domestic CAPM result in the same expected return as the use of global CAPM.This research is based on the previous research on the cost of capital in theinternational capital market conducted by Koedijk et al. (2002) and Karolyi and Stulz(2001) without the control variable the foreign exchange rate. The researcher did not usethis variable because it is assumed here that the perfect international financial market and “the law of one price”. This research focused on 413 stock from the eight Pacific Asiancapital markets during 1998 to 2003 periods. The research used purposive sampling andsimple regression statistic method. The research was conducted on the market level andindividual securities.The result of the research shows that on the most of the securities of the eight PacificAsian capital markets, there is no pricing error from the use of domestic CAPM when theuse of global CAPM is more appropriate. The security risk that is diversifiable domesticallyis also diversifiable globally. Consequently, the domestic market portfolio contains allinformation that is relevant to price assets. Generally, it can be concluded that the assetpricing of the Pacific Asian capital markets was priced domestically. The use of domesticCAPM is still relevant also shows a better performance than the global CAPM. Theimplication is that independent of the issue whether international capital markets are fullyintegrated, the domestic CAPM resulted in the same estimated return that the globalCAPM.Keywords: Estimated return, domestic CAPM, global CAPM, and pricing error, domesticmarket portfolio.